Evaluation of Mechanical Properties, Color Stability, and Cleaning Efficacy of BioMed Clear Resin‐Based Dental Aligners - Aisyah Safi'ai; Muhammad Imam Ammarullah; Muhammad Hanif Baharuddin; Nur Syafiqah Faidzul Hassan; Muhammad Hanif Ramlee (Engineering Reports)
ABSTRACT Clear aligners have gained widespread popularity as a comfortable and aesthetically appealing alternative to traditional braces; however, there is a lack of comprehensive research on the interplay between aligner thickness, color stability, and cleaning efficacy. This study addresses these gaps by systematically assessing the mechanical strength, color stability, and cleaning efficiency of BioMed Clear resin‐based aligners fabricated at different thicknesses. Seven aligner thicknesses, ranging from 0.50 to 1.10 mm, were designed and 3D‐printed using advanced scanning technologies. Mechanical compression testing revealed significant differences in compressive strength based on aligner thickness (p < 0.05), with the 0.60 mm thickness demonstrating optimal resistance. To assess color stability, aligners were exposed to stain solutions, where turmeric induced the most pronounced discoloration. Cleaning efficacy experiments indicated that gargling was the most effective agent for stain removal. These findings provide valuable insights into the optimization of aligner thickness for enhanced mechanical performance and patient comfort. Furthermore, the study highlights effective cleaning strategies to maintain oral hygiene and aligner aesthetics during orthodontic intervention. This research contributes to the advancement of aligner design and fabrication, offering evidence‐based recommendations for improving clinical outcomes in orthodontic practice.